2010
DOI: 10.2478/s11536-009-0143-1
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of pancreatic tuberculosis with systemic brucellosis: a case report

Abstract: AbstractIsolated pancreatic tuberculosis is an extremely rare clinical entity and is difficult to diagnose particularly in immunocompetent individuals. Clinical findings and symptomatology of brucellosis are often similar to tuberculosis thus making the differentiation amongst the two entities difficult. We report a case of pancreatic tuberculosis with systemic brucellosis in a 29 year old veterinarian who presented with epigastric pain and loss of appetite. Initial investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…This case also showed that when kidney involvement is present in brucellosis, urinary system infection could be also observed [7][8][9]. It was reported that renal involvement in brucellosis would improve without sequelae with appropriate treatment [9][10][11]. In addition, the presented case had symptoms of fever with rigors, left flank pain, and dysuria.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…This case also showed that when kidney involvement is present in brucellosis, urinary system infection could be also observed [7][8][9]. It was reported that renal involvement in brucellosis would improve without sequelae with appropriate treatment [9][10][11]. In addition, the presented case had symptoms of fever with rigors, left flank pain, and dysuria.…”
Section: Discussionmentioning
confidence: 59%
“…Although it is rare, brucellosis may present different focal complications in the urinary system. In the current literature although despite its rarety, it has been reported that pyelonephritis due to Brucella species may occur in different forms of brucellosis [7][8][9][10][11]. With this case presentation, we aimed to contribute the literature a case of Brucella pyelonefritis, who had complaints mimicking acute bacterial pyelonephritis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[16] [17]. The gold standard method in diagnosing brucellosis is blood culture, however, sensitivity is low among chronic cases.…”
mentioning
confidence: 99%